Microemulsions based on paeonol-menthol eutectic mixture for enhanced transdermal delivery: formulation development and in vitro evaluation. (18th August 2017) - Wang, Wenping; Cai, Yaqin; Liu, Yanhua; Zhao, Yunsheng; Feng, Jun; Liu, Chen
Abstract: In this work, microemulsion-based gels were prepared for transdermal delivery of paeonol. Microemulsions containing eutectic mixtures of paeonol and menthol were developed. The obtained microemulsions were evaluated for particle size, viscosity and physical stability. The selected microemulsions were incorporated into Carbopol gels. Drug crystallization behavior during a short-term storage was compared and in vitro permeation and deposition study were conducted on mouse skin. Results showed that the eutectic liquids of paeonol and menthol at all ratio (6:4, 5:5 and 4:6) could form microemulsions but with significantly different physical characteristics. As the ratio of paeonol increased, the prepared microemulsions exhibited larger droplet size, higher viscosity and quicker crystal growth. Microemulsion containing paeonol and menthol at a ratio of 4:6 possessed the smallest size of 27 nm. Accordingly, the related gel showed better physical stability during 10 days of storage, as well as the highest percent of drug deposition (111.8 μg/cm 2 ) and steady-state flux (0.3 μg/cm 2  h). These results suggested that the microemulsion formulation is a preferable approach for enhanced skin permeation, and the microemulsion based on drug–menthol eutectic mixture might be used as a potential transdermal delivery system for better therapeutic efficacy.